A SYSTEMATIC LITERATURE REVIEW: THE ROLE OF CIVIC EDUCATION IN INCREASING HONESTY BEHAVIOR OF ELEMENTARY SCHOOL STUDENTS - Nursyifa A. Wijaningsih; Yetty Auliaty (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2020)
Honesty behavior must be instilled through civic education learning and can be started from elementary school. This study aims to 1) identify the honest attitude of elementary school students; 2) identify civic education learning in elementary school students; 3) the application of civic education learning in developing the honest attitude of elementary school students. This study used a systematic literature review method in which all articles were processed based on inclusion, exclusion, and quality assessment criteria. It resulted in 14 primary articles analyzed with predetermined research questions. The results of the research in the form of the role of civic education in the development of honest attitudes have been widely studied by leading researchers from 2010 – to 2022. This research has implications for the discovery of subsequent research that can be used as a starting point for the following researchers interested in the theme of research regarding honesty in students.